(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2021)
Raja Bongsu’s significance in one of the most turbulent periods in the history of the sultanate Johor is the subject of this article. Seventeenth-century accounts play a major role in shaping the subsequent knowledge of him. These depict a man who—in a certain context—made decisions which to his own logic were right, but often led to serious problems. In the literature, he is an object of commentary rather than of study. Representations of Bongsu (youngest brother) establish the contours of his position, first as the closest associate of his brother, Sultan Ala’ud-din Ri’ayat Shah III (r. 1579–1615), and as Sultan Abdullah Ma’ayat Shah (r. 1615–1623). He was the Raja Ilir (from the downstream area), in the sources also referred to as Raja Seberang (the other side of the river where he had his fort and his constituency), actively engaging in Johor’s external relations, taking part in discussions and negotiations with foreigners on trade and military missions. His tenure coincided with the arrival and establishment of the Verenigde Nederlandse Oost Indische Compagnie (VOC), as an important factor in the Straits region.